Desain Tempat Tidur Anak dengan Kombinasi Hiburan dan Keamanan - Ali Muharom; Teddy Mohamad Darajat (MAVIS : Jurnal Desain Komunikasi Visual, 2025)
The diversity in the manifestation of gate architecture across the island of Java remains observable to this day. The Javanese people are widely recognized as a culturally rich society that continues to preserve and uphold its traditional values. The varied forms of gate structures are reflected in the differing characteristics of their constituent elements. This diversity is also evident upon entering the Ponorogo region of East Java, where one encounters entrance gates adorned with decorative motifs inspired by Reog, a traditional performing art that serves as a cultural emblem of Ponorogo. This study employs a qualitative approach with a descriptive research design to elaborate on the architectural characteristics of the Ponorogo Regency border gate, and is supported by Roland Barthes’ semiotic theory. Denotatively, the Ponorogo border gate functions as a physical boundary marker between administrative regions and serves as an entry point into the regency. On a connotative level, however, the gate carries symbolic meaning, acting as an architectural representation of regional identity. It also functions as a communicative medium, conveying specific cultural themes such as local philosophies, myths, and belief systems embedded within the community. The ornamental patterns and decorative elements serve as a visual reflection of Ponorogo’s cultural heritage. Therefore, the gate’s design embodies symbolic meanings that transcend its physical and functional form.